2021
DOI: 10.51620/0869-2084-2021-66-4-248-256
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics of uropatogenic isolates of Escherichia coli in hospitals

Abstract: The aim of the study was to evaluate the genetic affinity of uropathogenic E. coli cultures (UPEC) and to identify the major types of extended spectrum beta-lactamases (ESBL) found among nosocomial isolates. A molecular typing of UPEC (n=93) isolated from patients with urinary tract infections (UTI) who were hospitalised in nine medical facilities (MO) in Perm was performed. It was found that 69.89% of the cultures had individual RAPD/ERIC profiles, the remaining 30.10% were distributed among 13 genome groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Kluytmans et al (2013) reported the presence of bla CTX-M in 34, bla TEM in 9, and bla SHV in 1 of 44 ESBL-producing E. coli isolates obtained from humans (23). Similarly, another study stated that the bla CTX-M gene was found in 79.31% of isolates from patients with UTI, followed by bla TEM and bla OXA in 58.62%, while bla SHV was not observed in any of the samples (24).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Kluytmans et al (2013) reported the presence of bla CTX-M in 34, bla TEM in 9, and bla SHV in 1 of 44 ESBL-producing E. coli isolates obtained from humans (23). Similarly, another study stated that the bla CTX-M gene was found in 79.31% of isolates from patients with UTI, followed by bla TEM and bla OXA in 58.62%, while bla SHV was not observed in any of the samples (24).…”
Section: Discussionmentioning
confidence: 95%
“…They play the role of the primary causative factor of UTIs, which is one of the common nosocomial and community-acquired infections. Empirical antibiotic applications in the treatment of infection have triggered the development of MDR in pathogenic and commensal E. coli, including UPECs (24).…”
Section: Discussionmentioning
confidence: 99%
“…Trimethoprim mgrB [214] dfrA1, dfrA5, dfrA7, dfrA12, dfrA17 [226] dfrA8, dfrA14, dfr2d, dfrA3, dfrA9, dfrA10, dfrA24, dfrA26 [227] acrAB-tolC [213] Sulfamethoxazole sul1, sul2, sul3 [228] Fluoroquinolones gryA, gyrB, parC [217] qnrA, qnrB, qnrC, qnrS, qnrD, qnrE, qnrVC [219] aac(6 )-Ib-cr [223] acrB, [218] qepA, oqxAB [219] β-lactams mrdA [164] ampC [92] bla CTX-M , bla TEM , bla SHV [163], bla OXA , bla CMY [229] pAmpC [91] acrAB-tolC, acrAD-tolC [165] Table 3 shows resistant determinants of note for each antibiotic/antibiotic class stemming from either chromosomal gene mutation/deletion, antibiotic inactivation due to an enzymatic mechanism, or by efflux.…”
Section: Chromosomal Mutations Enzymatic Mechanism (Plasmid Encoded) ...mentioning
confidence: 99%
“…Similar findings were reported by Kuznetsova et al who noticed that bla OXA genes are present in 58.6% of ESBL phenotype-positive isolates. However, the most common β-lactamases belonged to the BlaCTX-M group (79.3%) [ 57 ]. Importantly, the B2 phylogroup is characterized as the most virulent type and, as mentioned before, together with the D phylogroup is responsible for the majority of UTIs [ 56 ].…”
Section: Multi-drug Resistance and Upecmentioning
confidence: 99%